Synthesis and sensing application of glutathione-capped platinum nanoparticles1. Issue 11 (7th June 2015) - Li, Wei; Zhang, Haixiang; Zhang, Jinli; Fu, Yan
<x xml:space="preserve">Abstract</x> Glutathione-capped Pt nanozymes are employed to explore colorimetric assays of Hg2+ in aqueous samples with ultrahigh sensitivity.